Identification And Antioxidant Activity Test Of Graptophyllum Pictum L. Griff Var. Viride Leaf Extract - Desi Fajrianti; Chaidir, Chaidir; M.Hanafi (SEAN Institute, 2024)
Flavonoids are one of the compounds that are effective as antioxidants and function to protect against exposure to free radicals. One of the plants that contain flavonoid compounds is the leaves of Graptophyllum pictum L. Griff Var. viride. This study was conducted to determine phytochemical screening, total flavonoids, total phenolics, and antioxidant activity analysis contained in the leaves of Graptophyllum pictum L.Griff Var. viride. This type of research is an experimental exploratory research. Extraction by multistage maceration using three solvents namely N-Hexan, ethyl acetate and 96% ethanol, antioxidant activity test with DPPH method, total flavonoid test using aluminum chloride colorimetric assay method, and total ph enol test using Folin-Ciocalteu method from Graptophyllum pictum L .Griff Var. viride leaves. The results of extraction with 400 g of Graptophyllum pictum L. Griff Var. viride leaf simplicia with N-Hexan, ethyl acetate, 96% ethanol respectively produced 4.5 g, 3.9 g, and 41.5 g of thick extract. The IC 50 values of N-Hexan, ethyl acetate, and ethanol extracts were 317.70 µg/mL, 227.30 µg/mL and 231.86 µg/mL, respectively. The total flavonoid content of N-Hexan, ethyl acetate, and ethanol extracts were 8.03; 55.52; 25.61mg quercetin equivalents/g extract, respectively. The total phenol content of N-Hexan, ethyl acetate, and ethanol extracts were 19,164; 16,135; 27,251 mg GAE/g extract, respectively.